Pelaksanaan Penyusutan Arsip Di Kantor Baperlitbang Kabupaten Karanganyar - Sello Fuji Prabowo; Patni Ninghardjanti; Nur Rahmi Akbarini (Politeknik Kampar, 2023)
This study aims to (1) Know the implementation of archive shrinkage (2) Know the supporting and inhibiting factors for archive shrinkage. (3) Data collection by observation, document analysis and direct interviews. The validity test technique used is triangulation of methods and data sources. Sampling techniques with Purposive Sampling and Snowball Sampling. Data analysis techniques used in research 1. Data Collection, (2) Data Reduction, (3) Data Presentation, (4) Conclusion Drawing and Verification. The results of the study are as follows: The archive depreciation activities carried out consist of: (1) Archive transfer activities from the Processing Unit / Creator Unit to the Main Archives Unit, and (2) Destruction of inactive dynamic archives that no longer have use value. The types of archives that are depreciated are all types of archives that can be depreciated but not all archives can be destroyed, for static archives it cannot be destroyed, but submitted to regional archival institutions. Meanwhile, dynamic archives can be destroyed by burning or shredding. Obstacles in archive shrinkage, (1) Difficulty in sorting archives, (2) Lack of expert staff, (3) Many archives are messy. Efforts to overcome obstacles (1) There is a clear policy and foundation related to archive shrinkage. (2) There is socialization and monitoring every year from the regional archive institution, namely Disarpus. (3) The existence of archival shrinkage in order to reduce the archives that accumulate in the office. Impact of archive shrinkage: (1) Optimizing the use of office space, (2) Reducing the need for storage space, and creating a more orderly and organized work atmosphere. (3) It is easier to manage archives, both static and dynamic archives, (4) Reduce archives that accumulate and those that are no longer used.